A holistic approach to tax administration performance management: Developing an integrated and open system model - Mansor, Muzainah; Tayib, Mahamad (Research Institute for Progression of Knowledge, 2015)
A tax administration can be viewed as an open system that transforms inputs into outputs within the internal and external environment in which it operates.Open system theory is the basis of an input-process-output-outcome model of performance management.However, an open performance management system alone is impracticable without integrating the strategic, operational, and individual performance management levels.Strategic and operational levels should support each other and have impact on how people act at the individual level.This paper proposes a holistic performance management model which combines an open system model with an integrated model to develop a new holistic performance management model as a guide for a tax administration to evaluate, improve and manage its performance management system.The new model integrates performance management at the strategic, operational and individual levels in an open system view of a tax administration.The distinct feature of the model is that it highlights the critical process of transforming inputs into outputs/outcomes in a tax administration by diagnosing the interrelation of the components in a tax administration process, i.e. formal organisation, informal organisation, task and people.These components contain both institutional and behavioural factors that should be carefully managed to improve the overall performance of a tax administration.